Code-Switching in Layangan Putus Film as a Resource for Digital Pedagogy in English Language Education - MASNIATI, ANDI; Margana; Noman (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2025)
This study examines the types and functions of code-switching used by characters in the Indonesian drama series Layangan Putus and investigates its potential as a resource for technology-enhanced English language education. Using a qualitative descriptive method, selected dialogues from the series were analyzed based on sociolinguistic frameworks to identify patterns of code-switching. The findings indicate that code-switching in the film serves expressive, referential, and interactional purposes, reflecting authentic bilingual communication in contemporary Indonesian society. Beyond its linguistic implications, this study emphasizes the pedagogical value of integrating film-based content into digital learning environments. Incorporating such media in English language classrooms can enhance students’ sociolinguistic awareness, cultural understanding, and communicative competence. The research contributes to both linguistic studies and the development of innovative, media-based approaches to English language teaching in the digital era.